Alternative frames of participation: the east-timor newsgroup. (9th December 2008) - Stewart, Charles
This case study of the east-timor newsgroup traces an alternative trajectory for participation on the internet. Through the appropriation of the technologies and spaces opened up by the processes of globalisation, political groups can rework globally mediated resources for specific local contexts. An assessment of the internal dynamics of the newsgroup models the genre as an adaptable communications tool for radical global democratic movements, to foment the development of strategies and tactics that are relevant for social change. The newsgroup is conceived as a discursive reproduction of 'real life' society, an extension of the social activist's space, contesting real opinions and real decisions. The east-timor newsgroup is evaluated on its ability to reveal a highly differentiated world of resistance, conflict, and uncertainty in the social formations of late capitalism and for its proclivity to open new fields of play where the dynamics have not yet rigidified and new kinds of socio-political movements are still possible.